Effect of mono- and dipotassium phosphate concentration on extracellular polysaccharide production by the bacterium Enterobacter A47. (December 2018) - Concórdio-Reis, Patrícia; Pereira, João R.; Torres, Cristiana A.V.; Sevrin, Chantal; Grandfils, Christian; Freitas, Filomena
Graphical abstract: Highlights: Lower phosphate concentrations reduced EPS production. Lower phosphate concentration decreased the EPS content in fucose. The polymer's Mw increased by lowering the phosphate concentration. Abstract: The fucose-rich exopolysaccharide (EPS) producer Enterobacter A47 was cultivated in medium containing different initial phosphate concentrations (3.0–8.8 g L −1 ) to evaluate the effect of this nutrient on EPS synthesis. Although cell growth was unaffected, a reduction of EPS production was observed upon lowering the phosphate concentration. The highest productivity, 1.57 g L −1  d −1, was achieved for a concentration of 8.8 g L −1, being reduced by 19 and 43% for the lower phosphate concentrations tested (5.8 and 3.0 g L −1, respectively). This decrease in bioproduction yield was also associated with modifications in composition and molecular weight (Mw) of the resulting polymers. The fucose content was reduced from 30 – 36%mol, for phosphate concentrations between 5.8 and 8.8 g L −1, to 26%mol for the lowest concentration tested. This change was concomitant with an increase of the polymer's Mw. These results demonstrated for the first time that EPS synthesis by Enterobacter A47 is affected by the medium's phosphate concentration, being favored by higher values that also result in unique polymers enriched in the rare sugar fucose.